2005
DOI: 10.1523/jneurosci.5155-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Activin mRNA and Smad2 Phosphorylation by Antidepressant Treatment in the Rat Brain: Effects in Behavioral Models

Abstract: Activin is a member of the transforming growth factor-␤ family that is involved in cell differentiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 44 publications
(61 reference statements)
7
69
1
1
Order By: Relevance
“…Enhancement of TGF-β signaling by activin, a member of TGF-β superfamily, promotes an antide-pressantlike effect (74). In the present study, SMAD4 expression is decreased by HSP-H, suggesting that the behavioral changes in the postpartum model could be precipitated by attenuated TGF-β signaling.…”
Section: Gene Expression Analysissupporting
confidence: 48%
“…Enhancement of TGF-β signaling by activin, a member of TGF-β superfamily, promotes an antide-pressantlike effect (74). In the present study, SMAD4 expression is decreased by HSP-H, suggesting that the behavioral changes in the postpartum model could be precipitated by attenuated TGF-β signaling.…”
Section: Gene Expression Analysissupporting
confidence: 48%
“…Embryonic neurons are dependent on the continual presence of growth factors for their survival while adult neurons may require trophic support only in times of injury (Benn and Woolf, 2004). Activin mRNA and protein are present at basal levels throughout the adult brain including cortical regions (Roberts et al, 1996) with significant upregulation of activin mRNA, its protein and activin signals in adult neurons can be detected within hours after injury (our data; Tretter et al, 1996;Dow et al, 2005;Bottner et al, 2006). Because activin administration protects adult hippocampal neurons from excitotoxic kainic acid and quinolic acid addition in vivo Tretter et al, 2000), it seems likely that increased amounts will improve neuronal survival after ischemic injury.…”
Section: Discussionmentioning
confidence: 64%
“…Variations in neural responsiveness to activin may be because of differences in receptor expression (Cameron et al, 1994;Funaba et al, 1997) or intracellular mechanisms activated by activin in neuronal phenotypes. One recent report suggests that activin mRNA and signaling, as well as behavioral improvements are also noted after antidepressant activity (Dow et al, 2005), but the mechanism of action in this case is not known. It Figure 6 mRNA changes after hypoxic exposure.…”
Section: Discussionmentioning
confidence: 82%
“…Although we report here that genetic disruption of activin signaling decreased anxiety-related behavior, a recent study showed that hippocampal infusion of activin exerted antidepressant-like activity in the forced swimming test. 56 Although caution is warranted when inferring abnormal emotional processing from altered behavior in animal tasks, it is tempting to speculate that, by tuning GABAergic neurotransmission, activin is essential to provide the optimal balance between anxiety and depression. In this scenario, activin signaling would adjust the level of anxiety to avert the daredevil behavior of dnActRIB mice, while, at the same time, preventing the behavioral immobility associated with depression.…”
Section: Discussionmentioning
confidence: 99%